2014
DOI: 10.1021/jm5003588
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Mechanisms of Action, and Toxicity of Novel 20(S)-Sulfonylamidine Derivatives of Camptothecin as Potent Antitumor Agents

Abstract: Twelve novel 20-sulfonylamidine derivatives (9a–9l) of camptothecin (1) were synthesized via a Cu-catalyzed three-component reaction. They showed similar or superior cytotoxicity compared with that of irinotecan (3) against A-549, DU-145, KB, and multidrug-resistant (MDR) KBvin tumor cell lines. Compound 9a demonstrated better cytotoxicity against MDR cells compared with that of 1 and 3. Mechanistically, 9a induced significant DNA damage by selectively inhibiting Topoisomerase (Topo) I and activating the ATM/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Notably, the four most promising compounds 15 , 24 , 27 and 31 showed broad in vitro antitumor spectra and were about 10- to 150-fold more potent than 3 . Furthermore, similar to our previous results, 32 the cytotoxic potencies of these derivatives were dual controlled by altering the length of the sulfonylamidine arm as well as the size of the substituent group. The best antiproliferative activity was achieved only with an appropriate balance between flexibility and size, such as in 15 , 24 , 27 , and 31 .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Notably, the four most promising compounds 15 , 24 , 27 and 31 showed broad in vitro antitumor spectra and were about 10- to 150-fold more potent than 3 . Furthermore, similar to our previous results, 32 the cytotoxic potencies of these derivatives were dual controlled by altering the length of the sulfonylamidine arm as well as the size of the substituent group. The best antiproliferative activity was achieved only with an appropriate balance between flexibility and size, such as in 15 , 24 , 27 , and 31 .…”
supporting
confidence: 88%
“…32 Among them, some new compounds displayed potent antitumor activity with significantly different drug-resistance profiles from those of irinotecan ( 3 , Figure 1), a clinically available anticancer drug. In addition, they also were effective in drug-sensitive and drug-resistant xenograft models at lower doses than 3 , demonstrating potential as drug candidates for anticancer chemotherapy.…”
mentioning
confidence: 99%
“…Esterification of the 20-hydroxy group also enhances plasma stability and augments in vivo antitumor activity compared with unmodified 1 . In continuing these efforts, we recently reported that a series of 20-sulfonylamidine camptothecin derivatives displayed potent antitumor activity with significantly different drug-resistance profiles from those of 1 [20]. Among them, 9 was more active than 3 against the growth of A549, DU-145, KB, and KBvin with IC 50 values of 0.031, 0.050, 0.14 and 0.026 μM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 6 The synthesis of compounds 6a-w and 7a-c is shown in Scheme 1. First, compounds 3a-e were obtained from the Ullmann reaction of 2,4-dichlorobenzoic acid 2 with anthranilic acid 1a or its derivatives 1b-e in DMF using Cu as the catalyst [16,17].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…While targeted anticancer drugs have been developed and clinically used, chemotherapy remains an important first-line treatment option for various cancers [2][3][4][5]. Therefore efforts have been continuously made for the development of more potent and less toxic anticancer chemotherapy drugs [6][7][8][9][10][11]. As part of the efforts in the discovery of potent antitumor agents, we have developed several series of new compounds such as aminopyrrolidine [12], tricyclic thiophene analogues [13] and acridine/acridone derivatives [14][15][16][17][18][19] with good antitumor activity.…”
Section: Introductionmentioning
confidence: 99%